PENINGKATAN LITERASI LINGKUNGAN DAN BERPIKIR KRITIS SISWA PERANGKAT PEMBELAJARAN BERDIFERENSIASI BERORIENTASI ESD PADA MATERI PERUBAHAN LINGKUNGAN - Prakoso, Teguh; Dewi, Endah Rita Sulistya; Hayat, Muhammad Syaipul (Jurnal Visi Ilmu Pendidikan, 2026)
This study aims to examine the effect of implementing differentiated learning tools oriented towards Education for Sustainable Development (ESD) on improving students' environmental literacy and critical thinking skills on environmental change material. The method used is quantitative with a true experimental design using a pretest-posttest control group design model. The research subjects consisted of two grades of 10 at SMA Institut Indonesia, selected randomly through random sampling techniques, each consisting of 32 students. The research instruments included a critical thinking ability test and an environmental literacy questionnaire administered before and after the treatment. Data analysis was carried out using paired sample t-test, independent sample t-test, and N-Gain calculation. The results showed that there was a significant difference between the pretest and posttest scores on both variables with a significance value of 0.000 (p < 0.05). The average N-Gain value for environmental literacy was 0.4083 and for critical thinking ability was 0.3893, both of which were in the moderate category. The independent sample t-test also showed a significant difference between the experimental and control groups, where the experimental group obtained higher results. These findings indicate that the implementation of ESD-oriented differentiated learning tools is effective in improving students' environmental literacy and critical thinking skills, as well as supporting the implementation of sustainable learning principles in schools.